2021
DOI: 10.1093/imrn/rnab001
|View full text |Cite
|
Sign up to set email alerts
|

Goeritz Groups of Bridge Decompositions

Abstract: For a bridge decomposition of a link in the $3$-sphere, we define the Goeritz group to be the group of isotopy classes of orientation-preserving homeomorphisms of the $3$-sphere that preserve each of the bridge sphere and link setwise. After describing basic properties of this group, we discuss the asymptotic behavior of the minimal pseudo-Anosov entropies. We then give an application to the asymptotic behavior of the minimal entropies for the original Goeritz groups of Heegaard splittings of the $3$-sphere an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…In that paper, a variation of Namazi and Johnson's result for the case of bridge decomposition was obtained: it was shown that the constant C for the finiteness of the Goeritz group can be taken uniformly to be at most 3796. The main result of the paper is the following, which improves the above mentioned result of [6].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…In that paper, a variation of Namazi and Johnson's result for the case of bridge decomposition was obtained: it was shown that the constant C for the finiteness of the Goeritz group can be taken uniformly to be at most 3796. The main result of the paper is the following, which improves the above mentioned result of [6].…”
Section: Introductionsupporting
confidence: 57%
“…Johnson [9] had refined this result by showing the constant C can be taken to be at most 4 independently of the genus of the Heegaard surface. The concept of Goeritz group has also been extended for bridge decompositions in [6]. In that paper, a variation of Namazi and Johnson's result for the case of bridge decomposition was obtained: it was shown that the constant C for the finiteness of the Goeritz group can be taken uniformly to be at most 3796.…”
Section: Introductionmentioning
confidence: 97%